Promoção de crescimento vegetal de Urochloa brizantha CV. BRS Piatã por compostos voláteis do fungo Trichoderma spp. - Sousa, Bianca Cristhiny Martins (Universidade Federal do Tocantins, 2020)
Fungi of the genus Trichoderma are fast growing filamentous that produce green colonies and present the potential to control phytopathogens and promote plant growth through the release of volatile compounds. Therefore, the objective of this study was to evaluate the effect volatile compounds of Trichoderma spp. im promoting grown of Urochloa brizantha cv. BRS Piatã. The experiment was carried out at the Federal University of Tocantins, Gurupi campus, where 10 seeds of the cultivar Urochloa brizantha cv. BRS Piatã in pots, which were previously filled with substrate and sand and autoclaved 30 minutes. Subsequently, four strains of Trichoderma spp. at the Microbiology Laboratory bank (Micro-Bio), the strains were picked and grown in plastic pots the were previously autoclaved and contained BDA culture medium, eight days after the culture emergence the polypropylene pots were attached to the bottom of the pots. A completely randomized design was used, beind 5 treatments, with 6 repetitions each. The data were submitted to the Scott-Knott test with 5% significance, and the evaluations were performed at 10 and 20 days after the docking, the variables related to legth (cm), fresh mass (g) and dry mass (g) of both shoot and root were evaluated. In the first evaluation the fungus Trichoderma asperellum obtained better results in relation to the length, fresh mass and dry mass of the shoot compared to other treatments. And in the second evaluation the same fungus and Trichoderma pinnatium obtained significant results in relation to shoot and root dry mass in relation to the other treatments, in the root length the results of the treatments did not differ statistically. Therefore, according to the results obtained Trichoderma spp. it is efficient in promoting plant growth by volatile compounds, and Trichoderma asperellum was the one that most differed statistically from other treatments.